The mobile pillars of sexual relationships. Pleasures and pressures: the practice of sexting in a gendered society amongst young people in South Africa. - Antonie, Cecile Olive (Centre for Film and Media Studies, 2019)
This dissertation investigates the diverse practices of sexting within the context of youth culture in South Africa. There is not yet a clear consensus on the definition of “sexting”, but in this case, it is understood as sending and receiving messages or images via social media that have sexual content, especially nude photographs. This research focuses on young heterosexual people in Cape Town from diverse socioeconomic backgrounds, exploring their motives and practices within the context of sexting. In this study 28 individuals aged 13 to 21 participated in in-depth, open-ended interviews which produced qualitative data. This research identifies and combines the theoretical works of Erving Goffman’s (1959) impression management theory and Marcel Mauss’s (1969) theory of gift-giving as lenses through which to study sexting. Both theories are still relevant due to the enduringly performative nature of social interactions. The data garnered from this study confirms that the rules of impression management and reciprocity and exchange apply in the era of social media in that sexting is a practice of social exchange whereby participants try to create the best possible persona, in order to form and secure relationships. Young people negotiate social obligations, status and power in a gendered society in relation to gift-exchange and reciprocity on mobile devices. The study further highlights that although sexism exists in this sphere of society, and sexting practices are fraught with gender inequities and double standards, young women are fighting to maintain a favourable online persona, by countering the derogatory term ‘fuck-boy’. Currently South African law prohibits sexting amongst minors, punishable as a crime. This dissertation argues that young people are motivated by pleasure and pressure to sext; excluding them from the public sphere of social media or trying to control their online sexual practice, is unlikely to prevent harm. Furthermore, humiliating or punishing minors for engaging in sexual activity online could be harmful in itself.